Giải pháp khắc phục tình trạng dạy thêm, học thêm tràn lan tại TP. Đà Nẵng - Huỳnh, Văn Hoa (2011)
Tác giả: Huỳnh Văn Hoa, ThS; Ngô Thị Thanh Nhung; Nguyễn Minh Hùng; Nguyễn Thị Minh Tâm; Nguyễn Bai; Võ Hồng Tiến -- Từ khóa: Dạy thêm; Học thêm; Đà Nẵng